New Wave Marketing and Reutilization of Out patient Services at “G” Clinic - Aziza, Nafra; Budiyanti, Rani Tiyas; Nandini, Nurhasmadiar (Journal of Public Health for Tropical and Coastal Region, 2025)
Introduction: In the competitive healthcare industry, G Clinic has demonstrated successful marketing practices through the New Wave Marketing (NWM) approach, resulting in a 17.4% increase in repeat visits from self-paying general patients. This study aimed to analyze the correlation between NWM dimensions and reutilization of outpatient services at the G Clinic. Methods : A quantitative cross-sectional study was conducted from March to June 2025 at G Clinic, Bekasi City. A total of 110 respondents were selected using accidental sampling. Data were collected through direct interviews (80%) and self-administered questionnaires (20%). Data were analyzed using the chi-square test, with NWM as the independent variable and decision to reuse outpatient services as the dependent variable. Results: Most respondents were young adults (40.9%) and female (65.5%). The majority attained a higher level of education (98.2%). The most common employment status was private sector employment (27.3%). The predominant range of total family income was IDR 5,000,000–IDR 7,999,999 (30.9%). There was a significant relationship between patients' decisions to return and all the NWM dimensions: strategy (p=0.000), tactics (p=0.000), and value-added (p=0.000). This finding highlights the importance of each element in building patient loyalty.Conclusion: The three dimensions of New Wave Marketing—strategy, tactics, and value-added— are associated with the decision to reutilize outpatient services at the G Clinic. It is recommended to develop engaging social media content, design service flow infographics, use the WhatsApp Business API, and launch a Patient Experience Highlight program. Other clinics should also showcase service catalogs on social media, monitor digital reviews, and apply consistent brand guidelines.